Antimicrobial Activity Test of Silver Nanoparticle Gel from Green Synthesis using Kelor Leaf (Moringa oleifera) as a Bioreductant Against Cutibacterium acne - Afrianse Pabuang; Rini Dwiastuti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Moringa oleifera leaves contain flavonoid compounds that have the potential to act as bioreducers in the synthesis of silver nanoparticles. The antibacterial activity of silver nanoparticles can reduce topical antibiotic resistance, especially against acne-causing bacteria. This study aims to determine the antimicrobial activity of silver nanoparticles formulated in a gel form at concentrations F1 10%, F2 20%, and F3 30%, using Medi-Klin Gel® as a positive control. Testing was conducted on Nutrient Agar medium using the paper disk method with Cutibacterium acne bacteria, incubated for 24 hours at 37°C. Additionally, physical evaluations of the gel, including organoleptic properties, spreading ability, and pH, were performed. The results of the physical properties of the gel were analyzed using one-way ANOVA. Organoleptic evaluation results indicated that F1 had a more transparent gel color, while F2 and F3 had darker gel colors, and all three gels had a characteristic extract aroma. Physical evaluation results for spreading ability (5.5±0.25; 5.7±0.12; 6.27±0.08) and pH values (4.42±0.17; 5.35±0.15; 5.27±0.17) were obtained. Antimicrobial research results showed inhibition zones for F1 10% (7.53±0.20), F2 20% (9.43±0.32), F3 30% (11.16±0.12), and the positive control Medi-Klin Gel® (25.15±0.26). Based on this study, concentration differences influenced the physical evaluation results of the gel formulation. Our finding suggests that the formula with the highest concentration (30%) has physical properties reaching the requirements and exhibited the highest inhibitory effect and potential as an antibacterial agent for acne.